Early screening of gestational diabetes mellitus using maternal hemoglobin A1C: Revision of current screening guidelines - Babak Pezeshki; Hossein Chiti; Peyam Arasteh; Saeedeh Mazloomzadeh (Babol University of Medical Sciences, 2019)
Background: HbA1C has been a known predictor and diagnostic test for diabetes type 2. However, this test has not yet been widely studied in GDM and more importantly no cutoff point has been defined for HbA1C in GDM. We investigated the efficacy of screening during first and second trimester of pregnancy and defined appropriate cutoff points according to HbA1C and FBS for predicting maternal GDM among women with none to minimal previously known risk factors. Methods: This is a prospective multi-centered cohort study. Individuals were evaluated at first trimester, at 20-24 weeks and 24-28 weeks of gestation. GDM tests were done during visits and accuracy of each of these measurements was evaluated. Results: Overall, 356 entered the study, among which 25 individuals and 30 individuals developed GDM during 20-24 and 24-28 weeks of gestation, respectively. HbA1C measured during first trimester at a cut-off of 5.35% predicted GDM of 24-28 weeks with an accuracy of 85.6%, sensitivity of 80%, and specificity of 80%. Furthermore, at a cut-off of 5.75% measured at 20-24 weeks, HbA1C predicted GDM with an accuracy of 94.5%, sensitivity of 97%, and specificity of 96%. Conclusion: Screening programs during first trimester and at 20-24 weeks of pregnancy, using HbA1C, can significantly aid in the early prediction of GDM, even among women with no to minimal previously known risk factors, which shows a need for revision in current guidelines.